Blood Pressure-Lowering Effect of Wine Lees Phenolic Compounds Is Mediated by Endothelial-Derived Factors: Role of Sirtuin 1 - Raúl López-Fernández-Sobrino; Jorge R. Soliz-Rueda; Javier Ávila-Román; Anna Arola-Arnal; Manuel Suárez; Begoña Muguerza; Francisca Isabel Bravo (Antioxidants, 2021)
The antihypertensive effect of wine lees powder (WLPW) from a Cabernet grape variety was related to its high content in flavanols and anthocyanins compounds. This study investigates the involvement of endothelial-derived factors and SIRT1 in its bioactivity. Spontaneously hypertensive rats (SHR) were orally administered water or WLPW (125 mg/kg bw). Posteriorly, both groups were intraperitoneally administered saline, Nω-nitro-L-arginine methyl ester (L-NAME), a nitric oxide (NO) synthesis inhibitor, indomethacin, a prostacyclin synthesis inhibitor, or sirtinol, an inhibitor of sirtuins. Blood pressure (BP) was recorded before and 6 h after WLPW administration. In an additional experiment, SHR were administered water or WLPW and endothelial expressions of eNos, Sirt1, Nox4, and Et1 were determined. The BP-lowering properties of WLPW were abolished by L-NAME and partially reduced by indomethacin, demonstrating that WLPW antihypertensive effect was mediated by changes in NO availability, although prostacyclin also contributed to this activity. Moreover, BP-lowering effect was reduced by sirtinol, indicating that WLPW decreased BP in a SIRT1-dependent manner. Furthermore, WLPW upregulated eNos and Sirt1 and downregulated Nox4 and Et1 endothelial gene expression. These results evidence the vasoprotective effect of WLPW and show that its antihypertensive effect in SHR is endothelium dependent and mediated by SIRT1.